2017
DOI: 10.7752/jpes.2017.01038
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of this study was to build a model for classification of motor and functional fitness in adolescent female students. To achieve this purpose, girls in 7 th (n=31), 8 th (n=26), and 9 th grade (n=28) were recruited with appropriate parental consent. To build the classification model, each adolescent performed and number of motor tests and the Stange, Genchi, Serkin tests of functional state. Canonical discriminant function analyses were conducted to determine the motor and functional fitness contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The study ascertained that the use of the combined method of strength development and the circuit training method in a one-month physical training cycle positively affected the overall development of motor abilities in the 6 th -8 th grade boys. The obtained results of the study characterize the peculiarities of the dynamics of middle schoolers' motor fitness and supplement the data of Ivashchenko et al [17], James et al [18] on the holistic character of motor abilities development in children and adolescents; the data of Blagrove et al [19], Prykhodko [20] on the regularities of motor abilities development in children and adolescents.…”
Section: Pedagogics Psychologysupporting
confidence: 78%
“…The study ascertained that the use of the combined method of strength development and the circuit training method in a one-month physical training cycle positively affected the overall development of motor abilities in the 6 th -8 th grade boys. The obtained results of the study characterize the peculiarities of the dynamics of middle schoolers' motor fitness and supplement the data of Ivashchenko et al [17], James et al [18] on the holistic character of motor abilities development in children and adolescents; the data of Blagrove et al [19], Prykhodko [20] on the regularities of motor abilities development in children and adolescents.…”
Section: Pedagogics Psychologysupporting
confidence: 78%
“…The works by Ivashchenko, Khudolii, Iermakov, Lochbaum, Cieślicka, Zukow, Nosko, and Yermakova, (2017), Ivashchenko, Khudolii, Yermakova, Pilewska, Muszkieta, and Stankiewicz, Błazej (2015) highlight the need for pedagogical control of the level of motor preparedness of schoolchildren; Ivashchenko, Yermakova, Cieślicka, and Śukowska (2015), argue that the level of coordination abilities development influences the effectiveness of teaching children and adolescents; points out the need for programming the development of coordination abilities.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we observed a high discriminant and predictive ability of the functions received: in assessing the motor preparedness of children and adolescents [33,34]; in the classification of strength loads among schoolchildren of junior grades [35,36]; in the classification of motor readiness, taking into account the level of training [24,37].…”
Section: Discussionmentioning
confidence: 96%